HALAL BRANDING STRATEGIES AND CONSUMER TRUST IN TIMES OF GLOBAL ECONOMIC UNCERTAINTY: A STUDY OF ISLAMIC SMES’ RESILIENCE IN RESPONSE TO PROTECTIONIST POLICIES - Aldriantara Sofyan; Kadar Nurjaman; Dudang Gojali; Iwan Setiawan; Iman Supratman (UIN Sunan Gunung Djati Bandung, 2025)
This literature review explores halal branding strategies and their impact on consumer trust, particularly within the context of global economic uncertainty. In recent years, protectionist policies have posed significant challenges to small and medium-sized enterprises (SMEs), including those in the Islamic sector. Halal branding has emerged as a key strategy for Islamic SMEs to distinguish themselves in the market, fostering trust and loyalty among consumers. The review examines existing literature on the role of halal branding in building consumer trust during times of economic instability. It highlights the resilience of Islamic SMEs in adapting to protectionist policies, focusing on the strategic responses to market fluctuations. The study identifies key factors that influence the effectiveness of halal branding in enhancing consumer trust, such as cultural values and ethical considerations. Moreover, the review discusses the intersection of halal branding and consumer behavior, emphasizing how trust can mitigate the impact of economic uncertainty. The literature also reveals the role of digital transformation in strengthening halal branding strategies for Islamic SMEs. In addition, the review assesses the long-term sustainability of halal branding in fostering business resilience. Finally, the paper concludes with recommendations for Islamic SMEs on leveraging halal branding to navigate economic challenges and enhance consumer trust.